Fusion gene bcr-abl: From etiopathogenesis to the management of chronic myeloid leukemia - Tri Agusti Sholikah (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Chronic Myeloid Leukemia (CML) is a myeloproliferative neoplasm. CML is relative frequent disorder. Most of CML patients have Philadelphia chromosome (Ph),which is derived from a reciprocal translocation between chromosome 9 and 22, t(9;22)(q34;ql1), generating the BCRABLfusion gene. In general, there are 3 breakpoint cluster regions in BCR gene : mayor(M-bcr), minor (m-bcr) and micro (μ-bcr). The BCR-ABL gene encodes proteins that vary in size depending on the breakpoint in the BCR gene. However, these proteins share a high tyrosine kinase activity. In the absence of activating stimuli, BCR-ABL tyrosine kinase able to transferphosphate from ATP (autophosphorilation) to tyrosine residues on various substrates in the cell. It actives intracelluler signaling pathways. These pathways cause increase proliferation or decrease apoptosis and differentiation of a hematopoietic stem cell; and defect in adherence of myeloid progenitors to marrow stroma resulting in CML. These discoveries determined that BCR-ABL fusion gene is critical event in etiopathogenesis of CML and a ideal target for therapy. Therapy of CML patients with BCRABL fusion gene-positif is by block autophosphorilation mechanism by Tyrosine Kinase Inhibitor (TKI), example imatinib. Molecular method to detect BCR-ABL transcript is necessary for monitoring response to TKI in CML pateints.